Effect of Organic and Biological Fertilizers on Biometric Indicators of Plant Growth, Development and Yield of Winter Wheat in Soils Contaminated With Heavy Metals - Boynazarov Baxron Raimovich; Djumaniyazova Gulnara Ismailovna (American Journal of Biology and Natural Sciences, 2024)
The article presents data on improving biometric indicators of growth and development of winter wheat plants in soils contaminated with heavy metals, as well as increasing the yield and quality of wheat grain using a complex of mineral, organic and biological fertilizers K-Gumat, Teria-S, Serhosil.